Anxiety and burnout in infectious disease nurses: the role of perceived stress and resilience - Yalan Huang; Zonghua Wang; Yongguang Li; Zhihan Zhao; Weiyi Wang; Changxia Cai; Xiushuang Wu; Li Liu; Mengting Chen (BMC Nursing)
Abstract Background Nurses serving in infectious disease ward represent a distinct occupational group that has attracted considerable attention following epidemic outbreaks. However, prior to this study, no research had delved into the underlying mechanism linking anxiety to burnout symptoms among infectious disease nurses. This study aimed to explore investigate the association between anxiety and burnout among nurses working in such environments and scrutinized the mediating role of perceived stress and the moderating influence of resilience on the principal relationship. Methods Employing a cross-sectional study using a web-based design, data were collected from 1,579 clinical nurses working in infectious disease ward across 50 hospitals in China. Participants responded to questionnaires assessing anxiety, perceived stress, resilience and burnout. Statistical analyses encompassed descriptive statistics, one-way analyses of variance, independent-samples t-tests, Pearson correlations, and bootstrapping techniques to evaluate the indirect and moderating effects. Results The study revealed that 62.13% of the respondents reported high levels of burnout, and 55.92% experienced moderate to high degrees of emotional exhaustion among infectious disease nurses. Significant correlations were observed between anxiety, perceived stress, resilience, and each component of burnout (P < 0.05). Notably, the mediating effect of perceived stress was accounting for 30.61% of the relationship between anxiety and burnout. Simple slope analysis demonstrated that perceived stress significantly predicted emotional exhaustion at both low (B = 0.854, t = 16.586, and P < 0.001) and high (B = 0.498, t = 9.503, and P < 0.001) levels of resilience. The perceived stress and emotional exhaustion were more serious when resilience levels were lower. Conclusion Anxiety was identified as a critical risk factor for burnout among nurses in infectious disease units. The relationship between anxiety and burnout was markedly affected by the levels of perceived stress and resilience. Specifically, the deleterious impact of perceived stress on burnout was amplified in nurses with diminished resilience relative to those with heightened resilience. Based on these findings, it is imperative to allocate resources for stress management programs and resilience training. Such initiatives would bolster support for nurses in infectious disease wards, ultimately enhancing their job satisfaction and well-being.